2018
DOI: 10.2147/cmar.s186108
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomal expression of long non-coding RNAs as diagnostic marker in bladder cancer

Abstract: BackgroundLong non-coding RNAs (lncRNAs) and exosomes have been regarded as components of cell signal transmission that modulate indigenous cellular microenvironments. Exosomes also participate in relocation of functional lncRNAs between cells.MethodsIn the present study, we evaluated expression of LINC00355, LINC00958, UCA1-201, UCA1-203, and MALAT1 lncRNAs in urinary exosomes isolated from transitional cell carcinoma (TCC) of bladder, non-malignant urinary disorders, and normal subjects.ResultsLINC00355, UCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 23 publications
0
79
0
Order By: Relevance
“…In the past decades, integrated medical-biological technologies were utilized to probe effective treatment method on patients with BLCA. 28 For instance, GAS5 tumor-suppressor lncRNA has been discovered the potential to improve the treatment outcome in patients with BLCA. 27 In addition, there is growing evidence that lncRNA might act as prognostic indicators in BLCA development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, integrated medical-biological technologies were utilized to probe effective treatment method on patients with BLCA. 28 For instance, GAS5 tumor-suppressor lncRNA has been discovered the potential to improve the treatment outcome in patients with BLCA. 27 In addition, there is growing evidence that lncRNA might act as prognostic indicators in BLCA development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have highlighted the role of long non-coding RNAs (lncRNAs) as urine-based biomarkers for diagnosis of bladder cancer [1,[10][11][12][13][14][15][16][17][18][19][20][21][22]. Long non-coding RNAs are transcripts longer than 200 nucleotides that are not translated into protein [23].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Another study [14] showed that overexpression of several lncRNAs, such as HOTAIR, HOX-AS-2, MALAT1, HYMAI, LINC00477, LOC100506688 and OTX2-AS1, has been found in urine exosomes of high-grade MIBC patients. Several other studies [10,12] also proposed various panels of lncRNAs as liquid biopsy biomarkers to discriminate bladder cancer patients from healthy controls.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 2 more Smart Citations